Criminal Behavior Patterns of a Serial Robbery Perpetrator: A Case Study - Baić, Valentina; Ivanović, Zvonimir M.; Cvetković, Davor (NBP. Nauka, bezbednosti, policija, 2025)
This paper examines a series of 24 robberies committed by a single offender, using data obtained from the Ministry of Internal Affairs, specifically the Police Directorate of the City of Belgrade. Through qualitative analysis of the offender’s criminal history and modus operandi, as well as frequency analysis and temporal-spatial distribution, the study provides a comprehensive insight into patterns of criminal behavior. The findings reveal distinct preferences regarding the time of offense (evening hours between 7 PM and 11 PM) and specific months (February and April), as well as geographical clusters of activity concentrated within certain Belgrade municipalities and streets. The analysis of the modus operandi highlights a consistent use of both planned and opportunistic strategies aimed at minimizing risk and maximizing gain. The results contribute to a deeper understanding of serial criminal behavior patterns, offering both theoretical and practical frameworks for the development of targeted preventive and operational strategies in policing practice.